Rapid and partial crystallization to design ductile CuZr-based bulk metallic glass composites. (5th February 2018) - Song, K.K.; Han, X.L.; Pauly, S.; Qin, Y.S.; Kosiba, K.; Peng, C.X.; Gong, J.H.; Chen, P.X.; Wang, L.; Sarac, B.; Ketov, S.; Mühlbacher, M.; et al.
Highlights: Rapidly and partially crystallizing CuZr-based bulk metallic glasses can control the precipitation of ductile crystals. Free volume annihilation induced during rapid annealing is slightly lower than those induced during slow annealing. CuZr-based metallic glass composites fabricated by rapid and partial crystallization show superior mechanical properties. Graphical abstract: Abstract: Transformation-induced plasticity in CuZr-based bulk metallic glass (BMG) composites opens up a new perspective for the design of ductile BMG composites. In this work, rapid and partial crystallization of BMGs is proposed to tailor microstructures of ductile BMG composites. During the early crystallization stage, the precipitation of B2 CuZr crystals in the Cu42 Zr42 Al10 Co6 BMGs is growth-controlled at low or high heating rates after having passed through a nucleation-dominated temperature region. Abundant nucleation is beneficial for the uniform precipitation of B2 crystals in the glassy matrix. Compared with annealing processes at slow heating, the degree of the free volume annihilation could be reduced to some content by employing a high heating rate. The microstructures of CuZr-based BMG composites can be effectively tuned by changing rapid annealing parameters, which enhances the ductility of the resulting BMG composites. This approach proves to be efficient for the development of ductile metastable alloys and composites.